Genotypic diversity effects on biomass production in native perennial bioenergy cropping systems - Morris, Geoffrey P.; Hu, Z.; Grabowski, P. P.; Borevitz, J. O.; de Graaff, M. A.; Miller, R. M.; Jastrow, J. D. (My University, 2015)
The perennial grass species that are being developed as biomass feedstock crops harbor extensive genotypic diversity, but the effects of this diversity on biomass production are not well understood. We investigated the effects of genotypic diversity in switchgrass (Panicum virgatum) and big bluestem (Andropogon gerardii) on perennial biomass cropping systems in two experiments conducted over 2008-2014 at a 5.4-ha fertile field site in northeastern Illinois, USA. We varied levels of switchgrass and big bluestem genotypic diversity using various local and nonlocal cultivars - under low or high species diversity, with or without nitrogen inputs - and quantified establishment, biomass yield, and biomass composition. In one experiment ('agronomic trial'), we compared three switchgrass cultivars in monoculture to a switchgrass cultivar mixture and three different species mixtures, with or without N fertilization. In another experiment ('diversity gradient'), we varied diversity levels in switchgrass and big bluestem (1, 2, 4, or 6 cultivars per plot), with one or two species per plot. In both experiments, cultivar mixtures produced yields equivalent to or greater than the best cultivars. In the agronomic trial, the three switchgrass mixture showed the highest production overall, though not significantly different than best cultivar monoculture. In the diversity gradient, genotypic mixtures had one-third higher biomass production than the average monoculture, and none of the monocultures were significantly higher yielding than the average mixture. Year-to-year variation in yields was lowest in the three-cultivar switchgrass mixtures and Cave-In-Rock (the southern Illinois cultivar) and also reduced in the mixture of switchgrass and big bluestem relative to the species monocultures. The effects of genotypic diversity on biomass composition were modest relative to the differences among species and genotypes. Our findings suggest that local genotypes can be included in biomass cropping systems without compromising yields and that genotypic mixtures could help provide high, stable yields of high-quality biomass feedstocks. © 2015 John Wiley & Sons Ltd.
Citation: Morris, G. P., Hu, Z., Grabowski, P. P., Borevitz, J. O., de Graaff, M. A., Miller, R. M., & Jastrow, J. D. (2016). Genotypic diversity effects on biomass production in native perennial bioenergy cropping systems. GCB Bioenergy. doi:10.1111/gcbb.12309
Article: Version of Record
Keywords: Big Bluestem; Biomass Feedstock; Cultivars; Ecotype; Fertilization; Low-Input High-Diversity